2001
DOI: 10.1152/jn.2001.85.4.1750
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Dynamics and Electrophysiological Properties of Cerebellar Purkinje Cells in SCA1 Transgenic Mice

Abstract: Cerebellar Purkinje cells (PCs) from spinocerebellar ataxia type 1 (SCA1) transgenic mice develop dendritic and somatic atrophy with age. Inositol 1,4,5-trisphosphate receptor type 1 and the sarco/endoplasmic reticulum Ca(2+) ATPase pump, which regulate [Ca(2+)](i), are expressed at lower levels in these cells compared with the levels in cells from wild-type (WT) mice. To examine PCs in SCA1 mice, we used whole-cell patch clamp recording combined with fluorometric [Ca(2+)](i) and [Na(+)](i) measurements in cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 36 publications
4
54
3
Order By: Relevance
“…This plateau was not observed in control cells (7 of 43 SCA1 cells vs 0 of 25 cells; p ϭ 0.041, Fisher's test). A similar plateau potential was previously described in most PCs from 3-to 6-monthold SCA1 mice (Inoue et al, 2001) and is suggestive of fast activation and inactivation of an A-type potassium conductance (IK A ) (Hounsgaard and Midtgaard, 1988;Klee et al, 1995). Accordingly, when recorded, this plateau current was reversibly abolished by low doses of 4-aminopyridine and could be recruited by a hyperpolarizing prepulse (Fig.…”
Section: Motor Impairment Precedes Morphological Changes and Loss Of supporting
confidence: 82%
See 2 more Smart Citations
“…This plateau was not observed in control cells (7 of 43 SCA1 cells vs 0 of 25 cells; p ϭ 0.041, Fisher's test). A similar plateau potential was previously described in most PCs from 3-to 6-monthold SCA1 mice (Inoue et al, 2001) and is suggestive of fast activation and inactivation of an A-type potassium conductance (IK A ) (Hounsgaard and Midtgaard, 1988;Klee et al, 1995). Accordingly, when recorded, this plateau current was reversibly abolished by low doses of 4-aminopyridine and could be recruited by a hyperpolarizing prepulse (Fig.…”
Section: Motor Impairment Precedes Morphological Changes and Loss Of supporting
confidence: 82%
“…4b). Interestingly, the proportion of PCs displaying this irregular plateau potential is higher in older SCA1 mice, as if its occurrence reflected the progression of the disease and was correlated with disease severity: 16% of PCs display the plateau in presymptomatic mice, 45% in early symptomatic SCA1 mice (5 of 11 vs 0 of 10 in controls; p ϭ 0.035, Fisher's test), and Ͼ80% in 3-to 6-month-old SCA1 mice (Inoue et al, 2001). IK A peak amplitude was isolated in PCs from presymptomatic SCA1 mice by the subtraction of potassium currents evoked by a depolarization to Ϫ20 mV after hyperpolarized (Ϫ80 mV) and depolarized (Ϫ40 mV) conditioning steps (200 ms) from a holding potential of Ϫ70 mV.…”
Section: Motor Impairment Precedes Morphological Changes and Loss Of mentioning
confidence: 96%
See 1 more Smart Citation
“…After the electrophysiological characterization, the PCs were labeled by dye injection via the recording electrode. All parameter values that we determined for the electrophysiological properties of control PCs ( Figure 4) were well in the range that has been described previously for PCs in rat and mouse brain slices and in vivo preparations (19)(20)(21)(22)(23)(24). The statistical comparison of these electrophysiological parameters between PCs of Afg3l2 PC-KO mice and their control littermates revealed no differences (Figure 4).…”
Section: Pc-specific Afg3l2 Deletion Causes Neurodegeneration and Secsupporting
confidence: 80%
“…Addressing intrinsic dendritic hyperexcitability is likely an important aspect of altered physiology which must be addressed in order to sustain benefit in the treatment of SCA, consistent with the critical role that intrinsic dendritic excitability plays in regulating synaptic integration 59. It is important to note that we and others have demonstrated that in association with dendritic degeneration, ATXN1[82Q] Purkinje neurons display increased subthreshold‐activated potassium channel currents2, 60 that affect spiking. Nevertheless, agents that reduce dendritic excitability through targeting these or other subthreshold‐activated potassium channels are beneficial in maintaining improvements in motor dysfunction at a stage of disease associated with dendritic degeneration.…”
Section: Discussionmentioning
confidence: 83%